Promoting inclusion and equity in Latin America: making sense of the challenges - Ainscow, Mel; Calderón-Almendros, Ignacio (My University, 2019)
Finding ways of including all children in schools is a challenge facing education systems throughout the world (Ainscow, 2016). In economically poorer countries this is mainly about the millions of children who are not able to attend formal education (UNESCO, 2015). Meanwhile, in wealthier countries many young people leave school with no worthwhile qualifications, whilst others are placed in special provision away from mainstream education, and some choose to drop out since the lessons seem irrelevant (OECD, 2012). Faced with these challenges, there is evidence of an increased interest in the idea of making education more inclusive and equitable. However, the field remains confused as to the actions needed in order to move policy and practice forward. This paper uses evidence from our experiences in five Latin America countries (i.e. Chile, Ecuador, Mexico, Paraguay and Uruguay) to address this agenda. In particular, we focus on the following questions: • What are the barriers that limit the participation and learning of some children in Latin American countries? • How can these barriers be best understood? • What does this mean for moving education systems forward? The analysis presented leads us to describe and reflect on the processes we have used to generate evidence in relation to these questions. As a result, we propose a framework that might be useful to those wishing to review the situation in other countries. We start, however, by outlining the contexts for our work.
Keywords: Educación; Inclusive Education